Ecotourism-Based Contextual Science Learning: The Potential of Sade Village as an Outdoor Science Laboratory - Neli Yuliani; Faridatunnisa; Lalu Firman Jundi Hidayatullah (Journal of Biology, Environment, and Edu-Tourism, 2026)
Science learning that is disconnected from real-world contexts limits students' ability to build a meaningful understanding of natural phenomena. Desa Sade, a traditional Sasak village in Central Lombok, offers rich, directly observable scientific phenomena embedded in its vernacular architecture, traditional weaving, and local ecological practices; however, its potential as a contextual science-learning resource remains systematically unexplored. This study aims to identify and describe the science-learning potential of Desa Sade ecotourism as a contextual science resource, based on direct field observations. A descriptive-exploratory qualitative approach was employed, using non-participant field observation. Data were analyzed using a qualitative-descriptive technique involving data reduction, narrative presentation linking phenomena to scientific concepts, and drawing conclusions based on the alignment between field findings and core scientific competencies. Results identified 13 distinct scientific phenomena across three domains: (1) vernacular architecture demonstrating thermal insulation in Alang-alang roofing and mechanical advantage in stone stairs; (2) traditional weaving illustrating subtractive color mixing and the biological properties of cellulose fibers; and (3) ecological practices, such as fermented buffalo manure flooring, providing a context for biological decomposition and microbial activity. These findings confirm that Desa Sade serves as a multi-disciplinary outdoor laboratory that bridges abstract concepts with authentic cultural contexts. Consequently, integrating ecotourism visits into middle and high school science curricula is highly recommended as a place-based pedagogical strategy to strengthen scientific literacy and cultivate sustainable cultural and environmental conservation values.